Microorganismos (Lactococcus lactis, Propionibacterium freudenreich y Debaryomyces hansenii) como alternativas a la bioconservación de alimentos. - Carrasco Arévalo, Héctor (2024)
The objective of this research was to study the microorganisms (Lactococcus lactis, Propionibacterium freudenreich and microorganisms (Lactococcus lactis, Propionibacterium freudenreich and Debaryomyces hansenii) as alternatives to food biopreservation. The methodology implemented was a bibliographic review of the last few years, using articles, tesis using articles, theses, web pages and the bibliographic manager such as zotero. The results obtained indicate that Lactococcus lactis is used in fermented cheeses and sausages, extending the shelf life of the product up to 50 and 45 days respectively. This biopreservative preserves sensory properties such as flavor, color and texture, and provides added protection against pathogenic bacteria, similar to that provided by sodium nitrate. On the other hand, Propionibacterium freudenreichii has a high efficacy in cheeses, extending the shelf life of the product up to 125 days, a period longer than the 45 days achieved by sodium nitrate, and encourages the formation of flavorful aromas and texture, considerably improving the quality of the product. Debaryomyces hansenii is used in cured meat, sausage and fermented meat. In cured meat it manages to extend the shelf life to 95 days, longer than the ninety days that ascorbic acid achieves; in sausage and fermented meat it obtains a shelf life of 50 days, longer than the 45 days of benzoic acid. It is recommended that research and development of the use of biopreservatives be encouraged, creating new food formulations and new combinations of biopreservative